Interrogating pollution sources in a mangrove food web using multiple stable isotopes - Souza, Iara da C.; Arrivabene, Hiulana P. [UNESP]; Craig, Carol-Ann; Midwood, Andrew J.; Thornton, Barry; Matsumoto, Silvia T.; Elliott, Michael; Wunderlin, Daniel A.; Monferrán, Magdalena V.; Fernandes, Marisa N. (Elsevier, 2018)
Anthropogenic activities including metal contamination create well-known problems in coastal mangrove ecosystems but understanding and linking specific pollution sources to distinct trophic levels within these environments is challenging. This study evaluated anthropogenic impacts on two contrasting mangrove food webs, by using stable isotopes (δ13C, δ15N, 87Sr/86Sr, 206Pb/207Pb and 208Pb/207Pb) measured in sediments, mangrove trees (Rhizophora mangle, Laguncularia racemosa, Avicennia schaueriana), plankton, shrimps (Macrobranchium sp.), crabs (Aratus sp.), oysters (Crassostrea rhizophorae) and fish (Centropomus parallelus) from both areas. Strontium and Pb isotopes were also analysed in water and atmospheric particulate matter (PM). δ15N indicated that crab, shrimp and oyster are at intermediate levels within the local food web and fish, in this case C. parallelus, was confirmed at the highest trophic level. δ15N also indicates different anthropogenic pressures between both estuaries; Vitória Bay, close to intensive human activities, showed higher δ15N across the food web, apparently influenced by sewage. The ratio87Sr/86Sr showed the primary influence of marine water throughout the entire food web. Pb isotope ratios suggest that PM is primarily influenced by metallurgical activities, with some secondary influence on mangrove plants and crabs sampled in the area adjacent to the smelting works. To our knowledge, this is the first demonstration of the effect of anthropogenic pollution (probable sewage pollution) on the isotopic fingerprint of estuarine-mangrove systems located close to a city compared to less impacted estuarine mangroves. The influence of industrial metallurgical activity detected using Pb isotopic analysis of PM and mangrove plants close to such an impacted area is also notable and illustrates the value of isotopic analysis in tracing the impact and species affected by atmospheric pollution.
Keywords: Food web; Metallurgic pollution; Neotropical mangroves; Trophic chain